Implementasi Bauran Pemasaran Dalam Upaya Meningkatkan Penjualan Pada Perusahaan Percetakan Tifa Grafika - Agum Al Ahmed; Baby Sri Murniyati Poernomo (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This study was driven by the increasing diversification of industrial businesses in Indonesia, within which theprinting sector has experienced intensifying competition, particularly in the digital era that has diminished thedemand for conventional printed materials. Despite this trend, the need for printing services persists,especially among educational institutions, government bodies, organizations, and small business enterprisesthat continue to rely on physical printing. This ongoing demand presents a strategic opportunity for printingbusinesses, including Tifa Grafika. However, in practice, Tifa Grafika has faced considerable challenges insustaining and expanding its customer base. Keywords: Marketing Strategy, Service Company, Printing Industry